2006
DOI: 10.2355/isijinternational.46.50
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aluminium Content on Thermophysical Properties of Ni-based Superalloys

Abstract: Ni 3 Al is the principal component in the gЈ phase formed in Ni-based superalloys but Ni 3 Cr and Ni 3 Fe can also contribute to the gЈ phase at temperatures below 820 K. Approximate values for the gЈ phase content can be derived from a relationship based on (mass% Al). In a previous publication it was shown that the density in both the solid and liquid alloys was dependent upon the gЈ phase (or Al) contents in the alloy. Consequently, the effect of the gЈ phase on other thermophysical properties (C p , enthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…(2) and (3), respectively) were also found to be functions of the Al content. It was also reported 2) that:…”
Section: Treatment Of Datamentioning
confidence: 85%
See 1 more Smart Citation
“…(2) and (3), respectively) were also found to be functions of the Al content. It was also reported 2) that:…”
Section: Treatment Of Datamentioning
confidence: 85%
“…In recent papers 1,2) it was found that: (i) physical properties of Ni-based superalloys were dependent upon the amount of gЈ phase formed. (ii) the amount of gЈ phase can be related to the Al content of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of the surface tension of the alloys relative to that of pure Ni is seen to result from the presence of Al although the reduction is much less than expected from an ideal mixing. In the bulk phase, the viscosity is dominated by the presence of the heavy alloying elements, while the effect of Al on the viscosity appears to be minimal [58] in comparison to what would be expected from an ideal mixture giving further evidence that in the liquid phase the composition of the free surface of the Ni-based superalloys is different from that of the bulk.…”
Section: à4mentioning
confidence: 86%
“…[9][10][11] Because of the large variety of Ni-based superalloys, predictive models for the values of a variety of thermophysical properties have been developed. [12] The models require reliable input data at selected alloy compositions to allow for proper scaling over a larger concentration range.…”
Section: Introductionmentioning
confidence: 99%
“…where κ is the thermal conductivity in W · m −1 · K −1 , σ e is the electrical conductivity in −1 · m −1 , and T is the absolute temperature in K. By using the Wiedemann-Franz law, the thermal conductivity of CMSX-4 alloy was calculated at room temperature to be 4.755 W · m −1 · K −1 , from the electrical-conductivity value of 65.13×10 4 −1 · m −1 [16]. At 1200 K, the thermal conductivity was 16.554 W · m −1 · K −1 , estimated from the electrical-conductivity value of 226.74 × 10 4 −1 · m −1 [16].…”
Section: Discussionmentioning
confidence: 99%